2003
DOI: 10.1074/jbc.m303164200
|View full text |Cite
|
Sign up to set email alerts
|

Human Combinatorial Fab Library Yielding Specific and Functional Antibodies against the Human Fibroblast Growth Factor Receptor 3

Abstract: The human combinatorial antibody library Fab 1 (Hu-CAL®-Fab 1) was generated by transferring the heavy and light chain variable regions from the previously constructed single-chain Fv library (Knappik, A., Ge, L., Honegger, A., Pack, P., Fischer, M., Wellnhofer, G., Hoess, A., Wö lle, J., Plü ckthun, A., and Virnekä s, B. (2000) J. Mol. Biol. 296, 57-86), diversified in both complementarity-determining regions 3 into a novel Fab display vector, yielding 2.1 ؋ 10 10 different antibody fragments. The modularity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 82 publications
(87 reference statements)
1
75
0
Order By: Relevance
“…HuCAL-Fab1, a fully synthetic human combinatorial antibody library 22,23 was used for in vitro selection of antibodies against rat TIMP-1 (data not shown, B. B., unpublished observations, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…HuCAL-Fab1, a fully synthetic human combinatorial antibody library 22,23 was used for in vitro selection of antibodies against rat TIMP-1 (data not shown, B. B., unpublished observations, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…FGFR3 is a candidate target to explain the effect of 17-AAG on synovial sarcoma. This protein not only has a documented role in promoting mesenchymal growth, but expression profiling studies from ourselves (6) and others (9) have highlighted expression of FGFR3 in synovial sarcoma, and furthermore, recent studies have shown antiproliferative activity of FGFR inhibitors in synovial sarcoma (16,22). Our data shows FGFR3 degradation is induced by 17-AAG, although we were unable to show growth inhibition by small molecule or antibody inhibitors of FGFR3 in our assays, which differed from the cited studies in that we did not use exogenous FGF ligand supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…36) that bind human IGF-I with low nanomolar affinity, in three panning cycles as previously described (37) and subsequently subjected to in vitro affinity maturation (38). IGF-IR antibodies used were aIR-3 (Calbiochem, No.…”
Section: Reagents and Cell Linesmentioning
confidence: 99%